2016
DOI: 10.1155/2016/1290561
|View full text |Cite
|
Sign up to set email alerts
|

Clonal Heterogeneity in the Neuronal and Glial Differentiation of Dental Pulp Stem/Progenitor Cells

Abstract: Cellular heterogeneity presents an important challenge to the development of cell-based therapies where there is a fundamental requirement for predictable and reproducible outcomes. Transplanted Dental Pulp Stem/Progenitor Cells (DPSCs) have demonstrated early promise in experimental models of spinal cord injury and stroke, despite limited evidence of neuronal and glial-like differentiation after transplantation. Here, we report, for the first time, on the ability of single cell-derived clonal cultures of muri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 46 publications
2
31
0
Order By: Relevance
“…Compared to control cultures maintained in the neural differentiation medium alone, ANDRO-treated ADSCs exhibited enhanced expression of the mature neuronal marker MAP2 [ 33 ] and β -tubulin III, which is an important structural protein for early neurons. While both ANDRO-treated and control cultures appeared to exhibit similar marker expression levels as assessed by immunofluorescence analysis, protein expression as estimated by Western blotting was significantly higher in cultures treated with 10 μ M ANDRO.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to control cultures maintained in the neural differentiation medium alone, ANDRO-treated ADSCs exhibited enhanced expression of the mature neuronal marker MAP2 [ 33 ] and β -tubulin III, which is an important structural protein for early neurons. While both ANDRO-treated and control cultures appeared to exhibit similar marker expression levels as assessed by immunofluorescence analysis, protein expression as estimated by Western blotting was significantly higher in cultures treated with 10 μ M ANDRO.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous work, we used human dental pulp stem cell (hDPSCs) as the experimental model to develop an in vitro system used to study proliferation and differentiation process [22]. hDPSCs represent a kind of adult mesenchymal stem cells that show the ability to differentiate in vitro in several multilineages such as odontoblasts, osteoblasts, chondrocytes, adipocytes and neurons [23,24,25,26,27,28,29,30]. The fact that hDPSCs can express basally PrP C [21] and show the ability to differentiate into neuronal-like cells [31] or dopaminergic neuron-like cells [32], prompt it to be considered as a cellular model for the study of neurodegenerative diseases, such as Alzheimer, Parkinson and Huntington diseases [22,33,34].…”
Section: Introductionmentioning
confidence: 99%
“…CD44, CD90, CD105, STRO-1) and are negative for hematopoietic markers (CD14, CD19), but capable of in vitro differentiation into odontoblasts, osteoblasts, chondrocytes, adipocytes and neurons [8][9][10]. Several works have shown that hDPSCs represent a highly heterogeneous population with distinct clones and differences in proliferative and differentiating capacity [11,12]. In particular, hDPSCs show the ability to differentiate into neuronallike cells [13] or dopaminergic neuron-like cells [14].…”
Section: Introductionmentioning
confidence: 99%